2019
DOI: 10.1109/lpt.2019.2904325
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the NEP of Mid-Infrared Upconversion Detectors

Abstract: We present a scheme to estimate the noise equivalent power (NEP) of the frequency upconversion detectors (UCDs), detecting mid-infrared (MIR) light. The NEP of UCD is a combined contribution of NEPs from the upconversion process and from the photodetector, used for detecting the upconverted signal. The 2 − 5 µm MIR range is particularly investigated in this letter using a bulk periodically poled lithium niobate based CW-intracavity UCD. We measured the NEP of UCD as 20 fW/ √ Hz at MIR wavelength of 3.39 µm. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The NEP remains an important factor of inquiry in the discussion of system NETD. For an MIR detector based on frequency upconversion, the NEP expression can be written as follows based on previous research work: 22 NEP=σRprΔf=σRηupηdethνMIRΔf=σRhνMIRηupηdetΔf,where ηup is the upconversion process quantum efficiency, ηdet is the CMOS camera quantum efficiency, Δf is the noise bandwidth, σR is the total readout noise, and νMIR is the MIR optical frequency. In the upconversion frequency converter, the main sources of noise are the Stokes noise of the shortwave pump, crystal thermal noise, image photon noise, and detector readout noise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NEP remains an important factor of inquiry in the discussion of system NETD. For an MIR detector based on frequency upconversion, the NEP expression can be written as follows based on previous research work: 22 NEP=σRprΔf=σRηupηdethνMIRΔf=σRhνMIRηupηdetΔf,where ηup is the upconversion process quantum efficiency, ηdet is the CMOS camera quantum efficiency, Δf is the noise bandwidth, σR is the total readout noise, and νMIR is the MIR optical frequency. In the upconversion frequency converter, the main sources of noise are the Stokes noise of the shortwave pump, crystal thermal noise, image photon noise, and detector readout noise.…”
Section: Methodsmentioning
confidence: 99%
“…In previous related work, the focus has often been on the evaluation of noise equivalent power. [21][22][23][24] This parameter is applicable to areas such as spectral detection, but is not intuitive enough for thermal imaging applications. The noise-equivalent temperature difference (NETD) is an important measure of the noise performance of conventional thermal imagers and is defined as the equivalent temperature difference between the target and the background when the signal-to-noise ratio of the image signal is 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the free space of electromagnetic radiation, the power flux density (PFD) is the power per unit area perpendicular to the direction of electromagnetic wave propagation, and its unit is W/m 2 [40], represented here by S. For the plane wave, power flux density, electric field strength (E) and magnetic field intensity (H) and the free space of the inherent impedance:…”
Section: The Minimum Detectable Power Of the System -Nepmentioning
confidence: 99%
“…Typically, higher upconversion efficiency improves the SNR. For detailed calculation steps of SNR and/or NEP see [106], [107]. By calculating or knowing the values of η, both isignal and σdet can be estimated.…”
Section: Noise Properties Of Upconversionmentioning
confidence: 99%
“…Dam et al [45] demonstrated single-photon imaging at an IR range of 3 µm, where they estimated an up-noise as low as 0.2 photons/spatial element/sec in a PPLN based intracavity upconverter. Very recently, Pedersen et al [107] compared the NEP of an upconversion detector and a cooled HgCdTe detector in the 3 µm range. With their upconversion detector having an overall detection efficiency (upconversion module + silicon detector, ) of 2%, they obtained a NEP of 20 fW/Hz 1/2 at 3.39 µm, which is 50 times better than the state-of-theart cooled HgCdTe detector of much higher efficiency 66%.…”
Section: Optical Noise Generated In An Upconversion Module (Up-noise)mentioning
confidence: 99%